Reflection Philosophical Legal Politics Of Determination Standard Tax Sale And Purchase Of Land According To Chambliss And Seidman's Perspective - Syainindita, Saraswati Asa; Subekti, Rahayu; Najicha, Fatma Ulfatun (Jurnal Ilmu Sosial Mamangan, 2024)
Land sale and purchase tax is one of the sources of local revenue regulated in the Law on Central and Regional Financial Relations. This provision is expected to be a means to increase regional fiscal independence. The problem arises when the government cannot set a minimum standard for the selling price of land owned by each person, so a mechanism is needed to ensure that the state can still obtain reasonable tax revenue from each land sale and purchase transaction. This study was conducted to see how the government carries out the legal policy to maintain the source of income derived from the land sale and purchase process. The analysis will be carried out using a normative legal research method supported by a conceptual and legislative approach. Various legal regulations related to the imposition of land sale and purchase tax will be studied using the legal realism perspective put forward by Chambliss and Seidman. This theory was chosen to show how social construction in Indonesian society and the influence of various aspects of life can affect the effectiveness of the imposition of land sale and purchase tax. The results of the study indicate that the government must set several standards, such as the percentage according to NJOP and the application of the Land Value Zone, to ensure that the amount of tax received can better reflect the value of legal certainty for the government. This study will provide an overview of the legal policy steps that can be used to standardize the imposition of taxes on similar economic processes.